Výskyt kmenů Klebsiella pneumoniae rezistentních k cefalosporinům III. generace na Dĕtské klinice Fakultní nemocnice v Olomouci - Kolár, M; Hájek, V; Kantor, L; Wiedermann, J; Koukalová, D (Epidemiologie, mikrobiologie, imunologie, 1995)
The authors describe the high incidence of strains of Klebsiella pneumoniae resistant to cephalosporins of the IIIrd generation at the department of pathological neonates of the Paediatric Clinic of the Faculty Hospital in Olomouc. They discuss possible reasons for this adverse situation and the way how to resolve it. They emphasize the necessity of rational administration of antibiotics and continuous monitoring of resistance in the most frequent causal agents of bacterial infections.
Keywords: Child; Klebsiella pneumoniae; rezistence k cefalosporinům; Humans; lidé; Cephalosporin Resistance; Klebsiella Infections; dítě; infekce bakteriemi rodu Klebsiella